Test-retest reliability of the emotional enhancement of memory. Issue 1 (2nd January 2020) - Schümann, Dirk; Joue, Gina; Jordan, Pascal; Bayer, Janine; Sommer, Tobias
ABSTRACT: Emotionally arousing stimuli are usually better remembered than neutral ones. This effect can be observed immediately after encoding and becomes more robust after a period of consolidation. The magnitude of this effect in an individual has been treated in various research contexts implicitly as reliable and temporally stable. However, we recently observed in 69 participants that an individual's memory advantage for negative over neutral stimuli, whether immediate or delayed, was very weakly correlated with the advantage measured after 3.5 years, albeit with slightly different memory paradigms. In the current study, we tested whether the test-retest reliability of these emotional memory effects might be larger if the temporal lapse between tests was shorter (10 weeks) and more similar memory tests were used. We observed that the better memory for emotional stimuli is highly replicable on the group level. However, the retest reliability on the individual level was very low. We replicated these findings by re-analysing data from a previous study where female participants took emotional memory tests at two different points of their menstrual cycle. We conclude, therefore, that the individual emotional enhancement of memory is not stable or that it cannot be measured reliably with the standard emotional memory paradigm.